The genome sequence of a sawfly, Athalia cordata Serville, 1823 [version 1; peer review: 2 approved] - Steven Falk; Andrew Halstead (Wellcome Open Research)
We present a genome assembly from a female specimen of Athalia cordata (sawfly; Arthropoda; Insecta; Hymenoptera; Athaliidae). The genome sequence has a total length of 169.00 megabases. Most of the assembly (99.98%) is scaffolded into 4 chromosomal pseudomolecules. The mitochondrial genome has also been assembled and is 27.47 kilobases in length.